ANTOLOGI PENGAUDITAN DAN KUALITAS AUDIT: STUDI PADA EMITEN TERINDEKS KOMPAS100 - Saifudin, Saifudin; Damayanti, Alvina Eka; Yulianti, Yulianti (Jurnal Akuntansi dan Pajak, 2024)
This study aims to examine the antologies in auditing and audit quality. The independent variables used in this study are audit tenure, auditor reputation, audit committee, audit fees, and company size. While the dependent variable in this study is audit quality as measured using the company's total accruals.The population in this study were manufacturing companies listed on the KOMPAS100 index on the Indonesia Stock Exchange for 2017 – 2021. The research sample was determined using a purposive sampling method so that the number of samples used was 165 out of 33 companies for 5 years. Multiple linear regression analysis was used as an analytical technique using IBM SPSS 24.The results of the study show that the auditor's reputation has an effect on audit quality. while audit tenure, audit committee, audit fees, and firm size have no effect on audit quality.